EXPERIMENTAL RESIDUAL STRESS OF 316 L/SA516 EXPLOSIVE WELDINGCOMPOSITE PLATE - SU WenXian; XIONG LiMin; GENG WanYi (Jixie qiangdu)
Explosive welding technology is a high-energy processing technology,which has been widely used in industrial practice. The residual stress produced by explosive welding process has an important influence on the strength and stability of the structure. So it is necessary to study the reasonable range of residual stress and seek to predict,control and adjust the residual stress. In this paper,the hole-drilling method is used to test the residual stress of 316 L/SA516 explosive welding plate. The basic principle of hole-drilling method for measuring the residual stress,the preparation of the test and the matters needing attention in the test process are introduced. The residual stresses measured by hole-drilling method mainlyanalysis explosive residual stresses,normalized residual stresses and residual stresses in the direction of explosive thickness. The development rule of the measurement results is basically consistent with the actual situation.